First data on Th–REE mineralization in mafic-ultramafic igneous rocks of the western slope of the Southern Urals - S. G. Kovalev; S. S. Kovalev (Georesursy, 2024)
The article presents the first data on rare earth mineralization in differentiated intrusions on the western slope of the Southern Urals. When studying the mineralogy of the rocks of the Shuida, Misaelga, Ishliy and Lysogorsk complexes, minerals of rare earth elements (monazite-(Ce) and allanite-(Ce), thorite (auerlite, cheralite)) and REEbearing minerals (zirconolite-(Y) and epidote). A detailed analysis showed that igneous monazite-(Ce) and allanite- (Ce) are significantly different from the metamorphogenic analogues previously described in various structural-material complexes of the region. It is concluded that rare-earth mineral formation in rocks of basic/ultrabasic composition is due to differentiation of the melt in the magma chamber. Close temperatures of formation of minerals from different complexes (Ishliy complex – 958°C, Shuida complex – 950–954°C, Misaelga complex – 947–952°C) testify to the identity of the processes of formation of monazite-(Ce) and allanite-(Ce). opinion, the chemistry of the environment of mineral formation.